Effect of Carbon Nanotube on Mechanical Properties of Jute Fibre Reinforced Polyester Composite - R.S.N. Sahai; Swagata R. Chaudhury; Deepankar Biswas (International Journal of Fracture Mechanics and Damage Science, 2024)
The current study studies how carbon nanotubes affect the mechanical characteristics of polyester composites reinforced with jute fiber, both treated and unprocessed. Alkali was used to cure jute textiles. Composites with treated and untreated jute fibre with 5%, 10% and 15% jute fibre loading with and without carbon nanotube were prepared using hand lay-up process. Carbon nanotubes varied from 0.2%, 0.4% and 0.6%. Tensile, flexural, and strength of impact all rise at higher fiber loading, whether or not nanotubes are being utilized. The 0.6% carbon nanotube reinforced alloy exhibits the highest rate of growth. Addition of carbon nanotube resulted in the enhancement in the mechanical properties due to strong interfacial bonding as indicated in SEM images.
Keywords: Carbon nanotubes; composite; jute fibre; nano fibers; polyester